AN UNUSUAL CAUSE OF ACUTE SMALL BOWEL OBSTRUCTION - Giri, Barsha; Kumar Mandal, Rajesh; Kumar Tamrakar, Kishor; Acharya, Bishal; Dhungana, Saroj (Journal of Chitwan Medical College, 2024)
Up to 20% of admissions with severe acute abdomen are due to intestinal obstruction, a common surgical emergency. Paraduodenal hernia is a rare entity of congenital internal hernia which is an unusual cause of small bowel obstruction. This case report describes the case of a 29-year-old woman with acute pain abdomen and vomiting without other significant past history. Radiological investigations revealed mechanical bowel obstruction and gangrenous bowel loops was evident on surgical exploration. Non-viable small bowel loop was resected and peritoneal defect was sutured. Left paraduodenal hernia is a rare cause of acute abdomen and high index of suspicion is required for early diagnosis and management.